A Comparison Between Software STAAD. Pro and Autodesk Structural Bridge Design for Swing Bridge - Mohd Hassan, Hanif Naufal; Zd. Zaibaftar, Nik Zikry; Khairul Anwar, Muhammad Syahir Darwish; Yahaya, Izat (Multidisciplinary Applied Research and Innovation, 2025)
Bridges are critical for contemporary transportation, particularly in logistics involving cargo ships and railroads. This research focuses on developing a swing bridge that connects routes for both trains and cargo ships, solving the issue of operating delays caused by disagreements between the two types of transportation. The swing bridge design was evaluated using STAAD.Pro and Autodesk Structural Bridge Design software. The investigation involved estimating the forces on the cantilever structure and assessing the bridge under dead and live loads. The study concluded that the swing bridge is an excellent choice owing to its high degree of safety, which is the consequence of a strong design and a constantly monitored rotating mechanism. The comparison investigation demonstrated that both software tools give credible insights into member forces and joint displacements, although with minor variances due to differing analytical approaches. The swing bridge improves logistical operations by allowing safe transit for trains and cargo ships, making it a viable option for future infrastructure projects.